Using sward height to manage pastures - Jochims, Felipe (2018)
Abstract - Pastures need to be managed with a proper herbage availability and keeping a proper residual mass when animals are removed from the area. This herbage has direct relation with the grass height and this residual mass is important due to the photosynthetically active leaves and their capacity in intercept the solar radiation, inﬂuencing the pasture regrowth without using the plant root reserves. Diﬀerent grass species present diﬀerent management heights, varying from 28cm to 14cm in Cynodons until 120cm to 60cm in Pioneiro elephant grass.